Pengembangan Pembelajaran Abad 21 Bagi Guru SMK - Tuti Iriani; Santoso Sri Handoyo (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose is to provide strengthening to vocational teachers regarding the scientific approach to 21st Century Learning. The results of previous research, which showed that 54.4% of teachers still used the lecture method in learning, meaning that teachers had not optimally carried out 21st century learning. This activity is carried out using the Zoom platform with materials 1) development of a scientific approach in 21st century learning and 2) Development of Cognitive, Affective, and Psychomotor Domains in 21st Century Learning. The pretest and post-test were conducted before and after the webinar. The results using the Wilcoxon test showed that significant differences in knowledge between before and after training. This showed that community service is able to increased teacher knowledge in the application of a scientific approach to 21st Century Learning.